Dr. Colbert's healthy gut zone - Colbert, Don (Siloam, 2021)
"Most chronic diseases actually begin in the gut. Did you know that there's also a powerful gut brain connection and whatever inflames your gut will eventually inflame your brain, causing memory loss, brain fog, fatigue, and invite all kinds of neurodegenerative diseases into your brain, but when you heal your gut, it helps to protect your brain."--